2014
DOI: 10.1002/chem.201304759
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Functionalized Trifluoromethylated Pyrrolidines, Piperidines, and Azepanes Starting from 1‐Tosyl‐2‐(trifluoromethyl)aziridine

Abstract: This paper reports on the generation and alkylation of the 1-tosyl-2-(trifluoromethyl)aziridin-2-yl anion with ω,ω'-dihaloalkanes, followed by a novel ring-expansion protocol toward 2-CF3-pyrrolidines, 2-CF3-piperidines, and 3-CF3-azepanes. A variety of halogen, oxygen, nitrogen, sulfur, and carbon nucleophiles was used to trigger this ring rearrangement, resulting in CF3-azaheterocycles bearing different types of functionalized side chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The chemistry of aziridines and aziridinium intermediates has evolved over the last few decades and their usefulness in synthetic chemistry relies mainly on their ability to undergo a nucleophilic stereo‐ and regioselective ring‐opening 7. 8 Particularly, 2‐(trifluoromethyl)aziridines were investigated by De Kimpe and co‐workers,9 who developed a selective synthesis of functionalized 2‐(trifluoromethyl)pyrrolidines E from 2‐substituted 1‐tosyl‐2‐(trifluoromethyl)aziridine D (Scheme ) 10…”
Section: Methodsmentioning
confidence: 99%
“…The chemistry of aziridines and aziridinium intermediates has evolved over the last few decades and their usefulness in synthetic chemistry relies mainly on their ability to undergo a nucleophilic stereo‐ and regioselective ring‐opening 7. 8 Particularly, 2‐(trifluoromethyl)aziridines were investigated by De Kimpe and co‐workers,9 who developed a selective synthesis of functionalized 2‐(trifluoromethyl)pyrrolidines E from 2‐substituted 1‐tosyl‐2‐(trifluoromethyl)aziridine D (Scheme ) 10…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the authors have also demonstrated that the chirality of the easily synthesizable vinyl aziridines could effectively be transferred to the fused azepine derivatives 579 and thus making the methodology highly desirable for the synthesis of fused azepines. Another recent report by D'hooghe and co-workers revealed a quite straightforward synthetic approach to various functionalized trifluoromethylated pyrrolidines 584, piperidines 585, and azepanes 586 starting from 1-tosyl-2-(trifluoromethyl) aziridine 580 (Scheme 146) [224]. The substrate could be easily synthesized in two steps from 3-amino-1,1,1-trifluoropropan-2-ol.…”
Section: Synthesis Of Seven-membered Rings From Activated Aziridines mentioning
confidence: 98%
“…13,77 The 2-aryl-3-(2-cyanoethyl)aziridines 221 furnish 3-aminopiperidines 222a and 222b through a regioselective ring-opening at the benzylic position due to the resonance stabilization of the developing benzylic carbenium ion at the C-2 position (Scheme 68). …”
Section: Synthesis Of Piperidines and Tetrahydroisoquinolinesmentioning
confidence: 99%
“…149 Later on, this group has described the ring-expansion of 2-(4-chlorobutyl)-1-tosyl-2-(trifluoromethyl)aziridine to azepanes (Scheme 86). 13 Of the two possible mechanisms, the first involved an initial cleavage of aziridine ring by alkyl amines at C . 150 It is worth mentioning that the reaction did not require any catalyst.…”
mentioning
confidence: 99%